(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The impact of Green Human Resource Management (GHRM) strategies on sustainability and performance indicators in Chhattisgarh’s Public Sector Undertakings (PSUs) is the focus of this study. To determine how four important GHRM practices—green recruiting, green training, green performance management, and green compensation—affect organisational performance, the research uses a multiple linear regression analysis. Results from a survey of 150 HR experts and workers from different PSUs show that implementing any GHRM practice improves organisational performance. This includes efficiency in operations, engagement among workers, and sustainability. The results show that sustainability objectives of PSUs may be advanced by incorporating environmental concerns into HR processes, which in turn improve performance indicators. To promote organisational excellence and sustainable growth in the public sector, this study stresses the significance of GHRM initiatives.